Selenium supplementation in heat-stressed poultry - Şahin, Kazım; Küçük, Ömer (My University, 2007)
Stress evoked by high ambient temperature results in economic loss through reducing feed intake while decreasing nutrient utilization, growth rate, egg production, egg quality and feed efficiency. Moreover, environmental stress leads to oxidative stress and reduces the antioxidant status of the bird in vivo, resulting in increased oxidative damage and lowered plasma concentrations of anti-oxidant vitamins (vitamin C, vitamin E) and minerals (zinc and selenium). Selenium is an essential trace element for animals and humans because of its role in the antioxidant enzyme glutathione peroxidase which protects cell membranes from damage caused by lipid peroxidation. Selenium deficiency causes several disorders in animal species and severe health problems in humans. Selenium supplementation has been found to eliminate selenium deficiency problems. Selenium is also used in the diets of heat-stressed poultry because of its reported benefits. This review deals with the effects of dietary selenium supplementation in poultry maintained at a high ambient temperature. © CABI Publishing 2007.
Keywords: Heat stress; Mineral supplementation; Poultry; Selenium